Knowledge of Drugs Abuse in Adolescent Girls (A case study of SEDA Nursing College, Surkhet) - Gautam, Sarswati (NPRC Journal of Multidisciplinary Research, 2025)
The drug abuse is the global issue in the present context. The objective of research is to find out status of knowledge regarding the drug abuse in adolescent age group, to recognize the status of knowledge regarding to drug abuse in adolescent age group, to evaluate the awareness level about drug abuse in adolescent age group and to examine the policy related to drug abuse. Altogether 65 adolescent’s girls were the respondents of the study. the respondents were selected through purposive sampling method. Some statistical tables were used to analyze and interpretation of data. The study was based on qualitative research design. A sizable proportion of individuals cited peer pressure as the key reason for beginning drug use. Some respondents cited their difficulty to reject friends and a desire to adhere to group norms as important reasons. Relationship breakdowns and personal loss were identified as major developmental drivers of drug misuse, among age-related changes, social pressures, and unemployment. The majority of respondents stated that mass knowledge is the most effective preventive method to address drug usage, while a smaller minority preferred the use of social media Participants had moderate awareness of Nepal's drug policies. However, the majority of respondents identified inadequate monitoring as the primary shortcoming in the policy's implementation, with others noting poor execution, a lack of cooperation with the government, and weak institutional structures. When questioned about major players in drug misuse prevention, several respondents underlined the importance of NGOs and INGOs, while others stressed the responsibilities of the government.